Skład gatunkowy, budowa i struktura oraz kierunki przemian drzewostanu z udziałem świerka w przygrzbietowej części rezerwatu Madohora w Beskidzie Małym - Karczmarski, Jan; Bąk, Paweł (Leśne Prace Badawcze, 2010)
This paper revisits a hilltop forest stand growing in the Madohora Reserve in Beskid Mały. The stand was first described by Myczkowski in 1955 as a spruce forest characteristic of the upper-montane forest zone. Based on the measurement of 11 circular study plots in 2005, new values for the following parameters were established: species composition, stand volume, stand basal area and storey structure, volume of both standing and fallen-dead trees, frequency and species composition of regeneration, as well as vitality and self-thinning of trees. The average stand volume in 2005 was 276 m3•ha-1, of which spruce comprised 67.5 %. Between the years 1955-2005, the proportion of spruce in the stand decreased by 30-50 %. In the lower storey and the regeneration, spruce is being replaced by intensively regenerating fir. This succession, as well as the poor vitality and high intensity of self-thinning of spruce, indicate that ongoing natural stand transformation is significantly reducing the proportion of spruce and may even result in its total elimination from the stand.